Applying strategic management to a family-based small medium enterprice : a case study on Hong Lian Gim Kee (HLGK) - Soong, Sarina (2012)
The rice wholesaling industry in Singapore is a rather saturated one, with a strong competitive landscape consisting of many dominant players that engage in extensive marketing to promote the brands they carry. Most distributors have been around for a long time and, hence, have a strong retailer network. Other than having strong networks, rice distributors need to provide convenience and accessibility to their products, have a strong brand following, and also have the right mix of pricing and promotional strategies to be successful in the industry.